2009
DOI: 10.1002/adma.200901168
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible‐Light Emission from Dye‐Doped Mesostructured Organosilica

Abstract: Efficient and color‐tunable visible‐light emission is achieved in fluorescent dye‐doped oligo(phenylenevinylene)–silica mesostructured films through fluorescence resonance energy transfer from a blue‐light‐emitting organosilica to a yellow‐light‐emitting dye (see figure). Tuning of the composition realizes pseudo white‐light emission with a quantum yield of 67%. Utilization of both walls and pores of the mesostructured organosilicas is effective to construct highly functional systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…This can be ascribed to ''in situ'' silane pre-functionalization, chemical dispersion on the molecular level, completely preventable movement [ 41 ] and agglomeration of high PL SiCD 1 , [ 25 ] and the excellent protective environment of the Ormosil host. Evidently, our SiCD-Gel glass monoliths are comparably bright and processable with the previously reported best QD-silica (QY = 35%), [ 13 ] QD-clay (67%), [ 42 ] and dye-Ormosil (76%) [ 11 ] composites, all of which were only thin fi lms.…”
Section: Communicationsupporting
confidence: 54%
See 1 more Smart Citation
“…This can be ascribed to ''in situ'' silane pre-functionalization, chemical dispersion on the molecular level, completely preventable movement [ 41 ] and agglomeration of high PL SiCD 1 , [ 25 ] and the excellent protective environment of the Ormosil host. Evidently, our SiCD-Gel glass monoliths are comparably bright and processable with the previously reported best QD-silica (QY = 35%), [ 13 ] QD-clay (67%), [ 42 ] and dye-Ormosil (76%) [ 11 ] composites, all of which were only thin fi lms.…”
Section: Communicationsupporting
confidence: 54%
“…[ 3 , 4 ] Among OIHMs, sol-gel derived organically modifi ed silicate (Ormosil) glasses embedded with functional dopants have attracted particularly attention, and can be applied in various optical materials and devices. [5][6][7][8][9][10][11] Ormosil glasses are expected a better choice as host materials for mechanical stability, facile preparation technique, and molecular level uniformity of dopants. They are also better than polymer matrices, especially for application in the fi elds of photonics and optoelectronics, because of their long-term, thermal stability [ 9 ] and designable microstructures.…”
Section: Organic-inorganic Hybrid Functional Carbon Dot Gel Glassesmentioning
confidence: 99%
“…11 Recently, several PMO materials with optical properties have been reported, and among them, PMO thin films show interesting potential for use as fluorescent materials. [12][13][14][15] For example, Goto et al investigated the fluorescence properties of aromatic-bridged PMO films and found that biphenyl-bridged PMO exhibited exceptionally high fluorescence quantum yield (0.45) compared with benzene-, naphthalene-, and anthracene-bridged PMO films (0.03-0.09). 12 A number of studies on biphenyl-bridged PMOs in powder form have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Inagaki and co-workers conducted pioneering work in which effi cient fl uorescence resonance energy transfer (FRET) was realized based on a coumarin-doped mesoporous organosilica fi lm with hybridized biphenyl groups within the framework. [ 283 ] The visible-light emission could be facilely tuned by optimizing the dye-loading amount. In addition, aggregation-induced emission (AIE) and aggregation-caused quenching (ACQ) chromophores were concurrently integrated into PMOs for effi cient multicolor emission based on the FRET ( Figure 26 ) mechanism.…”
Section: Mons For Bioimagingmentioning
confidence: 99%